2000
DOI: 10.1023/a:1005544518785
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Details are given of a new advanced theory of mind task, developed to approximate the demands of real-life mentalizing in able individuals with autism. Excerpts of films showing characters in social situations were presented, with participants required to answer questions on characters' mental states and on control, nonsocial questions. When compared with control participants, adults with high-functioning autism and Asperger syndrome were most impaired in their ability to answer the questions requiring mind-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(62 citation statements)
references
References 34 publications
4
56
0
2
Order By: Relevance
“…Therefore, our coding system differentiated whether the theory of mind response referred to cognitive, emotional or intentional mental states in the character. Our procedure was informed by standardized assessments of ToM processes using story-based stimuli and qualitative data collection (Heavey et al, 2000; Dziobek et al, 2006; Golan et al, 2006; Barnes et al, 2009; Dodell-Feder et al, 2013). We are also interested in exploring the way in which character depiction affects references to one’s own mental states (hereafter referred to as ToM-self).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our coding system differentiated whether the theory of mind response referred to cognitive, emotional or intentional mental states in the character. Our procedure was informed by standardized assessments of ToM processes using story-based stimuli and qualitative data collection (Heavey et al, 2000; Dziobek et al, 2006; Golan et al, 2006; Barnes et al, 2009; Dodell-Feder et al, 2013). We are also interested in exploring the way in which character depiction affects references to one’s own mental states (hereafter referred to as ToM-self).…”
Section: Introductionmentioning
confidence: 99%
“…Although formats such as the VAMA are more reflective of everyday social contexts than static pictures or story formats, it has been argued, rightfully, that they also rely on executive functions and central coherence, thus are not "pure" measures of ToM (Baron- Cohen, Wheelwright, & Jolliffe, 1997;Heavey, Phillips, Baron-Cohen, & Rutter, 2000;Roeyers, Buysse, Ponnet, & Pichal, 2001). The VAMA was designed to minimise demands on executive processes.…”
Section: Virtual Assessment Of Mentalising Abilitymentioning
confidence: 99%
“…Further, only the data from participants who responded correctly to control questions on the VAMA were included in the analyses. The VAMA's control questions were designed to detect deficits in executive functions and central coherence in that they involved the recollection and integration of film information without requiring social understanding (Heavey et al, 2000). Notwithstanding, future research involving clinical populations that have identified deficits in central coherence and executive functions (e.g., autism spectrum disorder and schizophrenia) is needed to explore the relative contribution of these processes to task performance.…”
Section: Virtual Assessment Of Mentalising Abilitymentioning
confidence: 99%
“…Na Imposing Memory Task (Kinderman et al, 1998) são apresentados cinco cenários sociais, no formato de histórias, seguidos por questões relativas à memória e competências de teoria da mente, de 1ª a 5ª ordem. No que diz respeito ao Awkward Moments Test (Heavey et al, 2000) e às tarefas desenvolvidas por Bosacki e Astington (1999), estas consistem na apresentação de situações sociais embaraçosas, em vídeo, e de cenários sociais apresentados através de histórias, respetivamente. Tal como nas tarefas anteriores, são colocadas questões aos indivíduos, que apelam à interpretação dessas situações e atribuição de estados mentais às personagens envolvidos, assim como à explicação dessas interpretações.…”
Section: A Tarefa Das Histórias Estranhasunclassified
“…Tal como nas tarefas anteriores, são colocadas questões aos indivíduos, que apelam à interpretação dessas situações e atribuição de estados mentais às personagens envolvidos, assim como à explicação dessas interpretações. A Imposing Memory Task (Kinderman et al, 1998) e o Awkward Moments Test (Heavey et al, 2000) foram ambos usados num estudo recente, com uma amostra normativa de adolescentes (Cavojová, Belovicová, & Sirota, 2011). O Story Comprehension Test (Channon & Crawford, 2000) envolve a apresentação de 12 histórias que representam situações sociais, perante as quais os participantes devem explicar o comportamento e/ou discurso de uma personagem.…”
Section: A Tarefa Das Histórias Estranhasunclassified